2018
DOI: 10.1089/jpm.2017.0205
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Supportive and Palliative Care Indicators Tool in a Geriatric Population

Abstract: SPICT seems to be valuable for identifying geriatric patients in need of palliative care as it demonstrates significant association with one-year mortality and with clinical survival predictions of experienced geriatricians, as reflected by TLDs given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
6
37
1
1
Order By: Relevance
“…48% of identified patients had died at 12 months, reasonably similar to our data here [16]. De Bock et al [24] found a sensitivity of 84.1% and a specificity of 57.9% for SPICT in a retrospective cohort study in a geriatric population general and clinical indicators performed equally in that study. The predictive value of the NECPAL CCOMS_ICO© tool was evaluated in a prospective, longitudinal study in primary care centres and a hospital in Spain in 1057 patients, with a mean age of 81 years and a 12-month mortality of 27.0%.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 89%
“…48% of identified patients had died at 12 months, reasonably similar to our data here [16]. De Bock et al [24] found a sensitivity of 84.1% and a specificity of 57.9% for SPICT in a retrospective cohort study in a geriatric population general and clinical indicators performed equally in that study. The predictive value of the NECPAL CCOMS_ICO© tool was evaluated in a prospective, longitudinal study in primary care centres and a hospital in Spain in 1057 patients, with a mean age of 81 years and a 12-month mortality of 27.0%.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 89%
“…The SPICT was chosen due to it is the only tool which is evidential of its ability to identify patients with palliative care needs early (6). Furthermore, the SPICT can be used in both inpatient and outpatient care (3).The SPICT is easily available through a web-based platform, is not restricted to specific diseases and has been translated and validated in different countries and healthcare settings in Europe (9)(10)(11). This study describes the process of translation, cross-cultural adaptation and content validation of the SPICT-SE.…”
Section: Introductionmentioning
confidence: 99%
“…SPICT is not restricted to specific diseases and has been tested in different settings (e.g. primary care, home care, and hospitals) 12,[16][17][18] .…”
Section: Mmentioning
confidence: 99%
“…The development, structure, and evaluation of the original English version of the SPICT™ have been described elsewhere 12 , as well as its use as a guide to help physicians recognize people at risk of deteriorating and dying 17,18 .…”
Section: Mmentioning
confidence: 99%